The effect of scatter and glare on image quality in contrast-enhanced breast imaging using an a-Si∕CsI(Tl) full-field flat panel detector - Carton, Ann-Katherine (American Association of Physicists in Medicine, 2009)
The purpose of this study is to evaluate the performance of an antiscatter grid and its potential benefit on image quality for a full-field digital mammography (FFDM) detector geometry at energies typical for temporal subtraction contrast-enhanced (CE) breast imaging. The signal intensities from primary, scatter, and glare were quantified in images acquired with an a-Si∕CsI(Tl) FFDM detector using a Rh target and a 0.27 mm Cu filter at tube voltages ranging from 35 to 49 kV. Measurements were obtained at the center of the irradiation region of 20–80 mm thick breast-equivalent phantoms. The phantoms were imaged with and without an antiscatter grid. Based on these data, the performance of the antiscatter grid was determined by calculating the primary and scatter transmission factors (T(P) and T(S)) and Bucky factors (B(f)). In addition, glare-to-primary ratios (GPRs) and scatter-to-primary ratios (SPRs) were quantified. The effect of the antiscatter grid on the signal-difference-to-noise ratio (SDNR) was also assessed. It was found that T(P) increases with kV but does not depend on the phantom thickness; T(P) values between 0.81 and 0.84 were measured. T(S) increases with kV and phantom thickness; T(S) values between 0.13 and 0.21 were measured. B(f) decreases with kV and increases with phantom thickness; B(f) ranges from 1.4 to 2.1. GPR is nearly constant, varying from 0.10 to 0.11. SPR without an antiscatter grid (SPR(−)) ranges from 0.35 to 1.34. SPR(−) decreases by approximately 9% from 35 to 49 kV for a given phantom thickness and is 3.5 times larger for an 80 mm thick breast-equivalent phantom than for a 20 mm thick breast-equivalent phantom. SPR with an antiscatter grid (SPR(+)) ranges from 0.06 to 0.31. SPR(+) increases by approximately 23% from 35 to 49 kV for a given phantom thickness; SPR(+) is four times larger for an 80 mm breast-equivalent phantom than for a 20 mm breast-equivalent phantom. When imaging a 25 mm PMMA plate at the same mean glandular dose with and without an antiscatter grid, the SDNR is 4% greater with a grid than without. For an 75mm PMMA plate, the SDNR is 20% greater with a grid. In conclusion, at the higher x-ray energy range used for CE-DM and CE-DBT, an antiscatter grid significantly reduces SPR and improves SDNR. These effects are most pronounced for thick breasts.